PENGGUNAAN GAYA BAHASA DALAM PROSA LIRIK PENGAKUAN PARIYEM KARYA LINUS SURYADI AG (KAJIAN STILISTIKA) - Ayu Fatmawati, Rita (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2019)
This study entitled Use of Language in Prose Lyrics Pengakuan Pariyem works Linus Suryadi Ag. Prose lyrics is one of the literary works in a variety of prose written and expressed by using the elements of poetry. Researchers only address two problems in this study, the comparison of style and stylistic contradictions. The theories used in this study is about stilistika, between the concept of stylistic comparisons that include, imagery, personification, metaphor, depersonifikasi, allegory, antithesis, redundancy and tautology, perifrasis, anticipation or prolepsis and correction or epanortosis. While the conflict style covers, hyperbole, litotes, irony, oxymoron, paralepsis, Zeugma and silepsis. The method used in this research is descriptive qualitative method because the data produced in the form of words in the form of quotations, not a number. Thus, the research report will contain excerpts sentences contained in lyric prose rich. Prose Lyrics Pengakuan Pariyem works Linus Suryadi Ag. Data uncovered by researchers in comparative form of citation style lyric Prose Lyrics Pengakuan Pariyem like words bak, ibarat, bagaikan, bila, pohon pohon mendengarkan, mentari nongkrong. While stylistic contradictions within quote the words of a sentence like menikam tajam ubun-ubun saya, gelinya setengah mati. The results of this study indicate that the use of force in the study of language stilistika a stylistic comparison and stylistic contradictions.